The role of gold acetylides as a selectivity trigger and the importance of gem-diaurated species in the gold-catalyzed hydroarylating-aromatization of arene-diynes - Hashmi, A. Stephen K.; Braun, Ingo; Rudolph, Matthias; Rominger, Frank (Organometallics, 2012)
Terminal 1,2-dialkynylarenes undergo an unexpected cyclization hydroarylation reaction toward naphthalene derivatives in benzene as the solvent. The regioselectivity of the reaction can be controlled by careful catalyst tuning. Also, the preparation of a bench-stable cationic amine complex or simple heterogenization of the catalyst on neutral aluminum oxide, which enables efficient catalyst recycling, was possible. Intensive mechanistic investigations were undertaken, giving new insights into the so-far underestimated role of acetylides in gold chemistry. The gold plays a fascinating dual role serving to both catalyze the reaction and activate the substrate by Au−C-σ bond formation. Evidence of gem-diaurated compounds playing an important part for gold catalysis is also reported.